Search for the pair production of scalar top quarks in the acoplanar charm jet final state in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2007)
A search for the pair production of scalar top quarks, (t) over tilde, has been performed in 360 pb(-1) of data from pp collisions at a center-of-mass energy of 1.96 TeV, collected by the D phi detector at the Fermilab Tevatron collider. The (t) over tilde decay mode considered is (t) over tilde -> c (chi) over tilde (0)(1), where (chi) over tilde (0)(1) is the lightest supersymmetric particle. The topology analyzed therefore consists of a pair of acoplanar heavy-flavor jets with missing transverse energy. The data and standard model expectation are in agreement, anda 95% C.L. exclusion domain in the (m((t) over tilde), m((chi) over tilde1)(0)) plane has been determined, extending the domain excluded by previous experiments. (c) 2006 Elsevier B.V All rights reserved.